Risk Management of Major Sporting Events: Implications for the 2008 Olympics - WU, Hao (2006)
Major sporting events such as Olympic Games, could usually benefit the host city from various ways. RM can make everything much more efficient and add value to organizers and relevant parties, to ensure their financial stability and facilitate them to meet the business target. RM can be viewed on operational level, project level, programme level and strategic level. Major sporting events could be generally regarded as huge government projects and benefit from project risk management process. The purpose of this dissertation is to analyze the key risks and risk management solutions on major sporting events. Case study, interview, telephone consultation was applied to get useful data for this dissertation. Case study of Athens 2004 Olympics aims at analyzing risk management experience from the previous sporting events, and the purpose of two interviews and telephone consultations is to get primary data about risk management efforts of Beijing 2008 Olympics. Despite of many efforts have done by BOCOG, some potential problems could not be ignored. Chinese government may still have to make improvements on market efficiency, enhance regulations and legislations. Furthermore, a long-term view is always needed for further development after Olympics.